Regional economic impact of Covid-19: The role of sectoral structure and trade linkages - Philipp Meinen; Roberta Serafini; Ottavia Papagalli (European Central Bank (ECB), 2021)
The paper provides an ex-post analysis of the determinants of within-country regional heterogeneity of the labour market impact of COVID-19. By focussing on the first wave of the pandemic in the four largest euro area economies, it finds that the propagation of the economic impact across regions cannot be explained by the spread of infections only. Instead, a region's economic structure is a significant driver of the observed heterogeneity. Moreover, our results suggest that a region's trade relations, both within and across countries, represent a relevant indirect channel through which COVID-19 related disruptions affect regional economic activity. In this regard, the analysis depicts vulnerabilities arising from potential disruptions of the highly integrated EU supply chains.
Keywords: R11; F14; J40; R15; 330; COVID-19 pandemic; short-time work; input-output linkages; sectoral exposure; regional differences